Study of the retention behavior of small polar molecules on different types of stationary phases used in hydrophilic interaction liquid chromatography. Issue 11 (19th April 2014) - Vlčková, Hana; Ježková, Kateřina; Štětková, Kateřina; Tomšíková, Helena; Solich, Petr; Nováková, Lucie
<x xml:space="preserve">Abstract</x> The retention behavior of a large group of analytes (35) with varied properties (pKa and logP) was studied on eight hydrophilic interaction LC columns with different surfaces, stationary phase chemistries, and types of particles. The acetonitrile content (5–95%), buffer concentration (0.5–200 mM), and pH of the mobile phase (3.8 and 6.8) were evaluated for their effects on the retention behavior. The type of stationary phase had a significant impact on the selectivity and retention time of the tested analytes. Completely different selectivity was observed on the aminopropyl stationary phase. In this study, the influence of the buffer concentration was similar for all tested columns, except for the aminopropyl stationary phase. Increasing the buffer concentration led to decreased retention times for the basic compounds and increased retention times for the acidic compounds, while the inverse behavior was observed on the aminopropyl stationary phase. The selectivity of the individual stationary phases was evaluated at pH 3.8 and 6.8. Much lower selectivity differences between the stationary phases were observed at pH 6.8 than pH 3.8. Bare silica stationary phases were used in the comparison of the particles (fused‐core and fully porous particles of 3 and 1.7 μm) and the columns provided by different manufacturers.